Remote monitoring to address obesity: experiences in nursing (Research, Society and Development, 2021)
Introduction: Obesity is a complex chronic disease that threatens public health in many countries, being considered as a global epidemic of the 21st century by the World Health Organization (WHO), conditioned mainly by the food and physical activity profile.Objective: To investigate which are the main tools used for the remote monitoring of individuals with obesity by the nursing team and analyze them. Method: Integrative review carried out in 2020. The search strategy was for studies in English and Portuguese, published between April 2014 and April 2020, structured with the descriptors: Telenursing; Telemonitoring; Biomedical Technology; Obesity and nursing. Results: Six studies were selected for analysis. The tools used by the studies to perform remote monitoring of obese individuals were telephone contacts, a mobile application, sending e-mails, and sending push notifications. Conclusion: Web-based digital interventions are effective in terms of weight loss, body fat, waist circumference and BMI, in studies ranging from six months to 12 months. In addition to intervening in the lifestyle of the population and establishing a better quality of life.